Bengkayang EFL Teachers’ Strategies to Motivate Secondary School Students to Learn English - Elisathusilawani Elisathusilawani; Listyani Listyani; Joseph Ernest Mambu (Soegijapranata Catholic University, 2025)
This study investigates the strategies employed by novice English as a Foreign Language (EFL) teachers in Bengkayang Regency, West Kalimantan, to foster student motivation in secondary schools. Grounded in the understanding that extrinsic motivation plays a crucial role in language acquisition, this research explores how these teachers, many of whom are former scholarship recipients themselves, leverage their experiences to address the specific challenges faced by students in a resource-limited environment. Data were collected through questionnaires, semi-structured interviews, and Focus Group Discussions (FGD) revealed that these teachers primarily utilized strategies such as understanding students' personal life, understanding students' needs, creating a supportive and positive learning atmosphere, and integrating technology into the teaching and learning process. Thematic analysis of interviews revealed effective teaching practices, offering practical guidance for educators in comparable contexts. This research ultimately seeks to contribute to a more nuanced understanding of EFL pedagogy in Bengkayang